2018
DOI: 10.1016/j.bbmt.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Higher Peak Tacrolimus Concentrations after Allogeneic Hematopoietic Stem Cell Transplantation Increase the Risk of Endothelial Cell Damage Complications

Abstract: Noninfectious transplantation-related complications (TRCs) such as graft-versus-host disease (GVHD) and endothelial cell damage (TRC-EC) are critical after allogeneic hematopoietic stem cell transplantation. Tacrolimus (TAC) is used to control GVHD. Hypertension and renal failure are common adverse events after TAC treatment. Higher blood concentrations of TAC would be expected to reduce the risk of GVHD but may increase TRC-EC. TRC-EC often develops in patients with GVHD; thus, it is difficult to clinically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Additionally, bacterial endotoxins [lipopolysaccharide (LPS)] move through damaged intestinal mucosa and can increase EC activation. Other agents used during HCT, such as sirolimus and calcineurin inhibitors (CNIs; ciclosporin, tacrolimus), potentiate endothelial injury and accelerate senescence 17,44,45 . Higher peak tacrolimus concentrations after transplantation increase the risk of HCT complications related to endothelial damage 45 …”
Section: Factors Leading To Endothelial Damagementioning
confidence: 99%
“…Additionally, bacterial endotoxins [lipopolysaccharide (LPS)] move through damaged intestinal mucosa and can increase EC activation. Other agents used during HCT, such as sirolimus and calcineurin inhibitors (CNIs; ciclosporin, tacrolimus), potentiate endothelial injury and accelerate senescence 17,44,45 . Higher peak tacrolimus concentrations after transplantation increase the risk of HCT complications related to endothelial damage 45 …”
Section: Factors Leading To Endothelial Damagementioning
confidence: 99%
“…It has a reported overall mean incidence of 8% to 14%, with an incidence of up to 60% in some high-risk populations [1][2][3]. VOD/SOS occurs as a result of activation and damage of the sinusoidal endothelium [4,5]. VOD/SOS with multiorgan dysfunction (MOD; renal and/or pulmonary) is reported to be associated with >80% mortality when treated with supportive care alone [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Ganetsky et al reported that TAC concentration 1 week after HSCT, performed with either HLA‐matched or unmatched donors, is associated with the occurrence of aGVHD, but this association is lost in the second to fourth weeks 4 . Recently, we reported that higher peak TAC concentration (>13.5 ng/mL) at week 3 may accelerate the risk of transplantation‐related complications with endothelial cell damage (TRC‐EC), but that this was not associated aGVHD incidence 3 . Although several studies reported the utility and importance of assessing mean TAC concentration, the optimal range of mean TAC concentration and intervention time period still remain to be elucidated.…”
Section: Discussionmentioning
confidence: 81%
“…Although TAC is valuable for GVHD prophylaxis, it has a narrow range of therapeutic concentrations, and its clinical use is complicated by its pharmacokinetic variability 2 . Moreover, previous studies have shown that inappropriate concentrations of CNIs immediately after allo‐HSCT may result in aGVHD and other non‐infectious transplantation–related complications (TRCs) 3‐6 . Therefore, therapeutic drug monitoring (TDM) is essential.…”
Section: Introductionmentioning
confidence: 99%